2015
DOI: 10.5152/akd.2014.5561
|View full text |Cite
|
Sign up to set email alerts
|

Mitral annular plane systolic excursion in the assessment of left ventricular diastolic dysfunction in obese adults

Abstract: Objective:Mitral annular plane systolic excursion (MAPSE) is a simple way to assess left ventricle (LV) function. MAPSE is also correlated to parameters, illustrating the close relation between systolic and diastolic function of LV. In this study, we evaluated whether MAPSE could help us in the determination the LV diastolic dysfunction (DD) in obese adults.Methods:Our study was a prospective cross-sectional study. Obese patients who were referred from the endocrinology clinic were enrolled into this study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Patients in this study showed a marked decrease of LV ejection fraction (EF) measured by auto LV EF compared to the control, similar findings were reported by Koestenberger et al, Bergenzaun, and Taşolar et al [15], this may support that EF is an easy, sensitive tool for evaluation of LV systolic function [16,17,15]. In the current study speckling tracking echocardiography was used to measure the sphericity index of the left ventricle.…”
Section: Like Other Previous Studies Mcmahon Et Al Andsupporting
confidence: 88%
“…Patients in this study showed a marked decrease of LV ejection fraction (EF) measured by auto LV EF compared to the control, similar findings were reported by Koestenberger et al, Bergenzaun, and Taşolar et al [15], this may support that EF is an easy, sensitive tool for evaluation of LV systolic function [16,17,15]. In the current study speckling tracking echocardiography was used to measure the sphericity index of the left ventricle.…”
Section: Like Other Previous Studies Mcmahon Et Al Andsupporting
confidence: 88%
“…The diagnosis of subclinical LV systolic dysfunction can be detected by assessing MAPSE. MAPSE was significantly reduced in patients with chronic heart failure, with a good correlation between MAPSE and EF 17 19 . Among our patients the mean MAPSE was comparable between SCD and controls and was higher in βTM patients (p=0.019) when compared to SCD and controls.…”
Section: Discussionmentioning
confidence: 87%
“…Diastolic function can also be assessed with it, i.e. in obese adults with normal LV EF [ 10 ]. Furthermore, even when performed by an untrained observer MAPSE measurements were found to be a highly accurate predictor of EF [ 11 ].…”
Section: Introductionmentioning
confidence: 99%